Compton's encyclopedia and fact-index; Vol.4 (C - Chid) (Compton's Learning, 1995)
There is an enormous amount of information in the 26 volumes that make up Compton's Encyclopedia. Volume 26 contains the unique Fact-Index - a miniencyclopedia that takes indexing into another dimension of information. Within the main-text articles in the other 25 volumes are valuable study aids - photographs and highly detailed maps and drawings, previews, fact finders, fact summaries, fact boxes, tables of terms with definitions, bibliographies and profiles of interesting people, places, things, and concepts. There are also more than 2.000 tables and other features and thousands of cross-references in both the main text and the Fact-Index